MODEL UNTUK PENETAPAN TARIF ZONA PARKIR (STUDI KASUS KOTA PADANG) - Asrizal Asrizal (Jurnal Rekayasa Sipil (JRS-Unand), 2015)
Parking problem in Central Business District (CBD) of Padang City is the use of parking space on the roadside, especially on the Pasar Raya street that has exceeded capacities. Meanwhile, request of the parking space on the roads surrounding is still below the available capacity. To balance the demand and supply of the parking space in this area, a research is conducted to make a change of parking management through applying different tariff for different zones of parking. Tariff of parking in zone which have been identified, is calculated with equation of linear regression model which pursuant to probability of Willingness to Pay by service users. The antecedent survey which conducted to some respondent, indicate that factors such as tariff, distance, duration and accessibility, having an effect which enough to influence the probability of service user in choosing of location of parking. All factors did not correlate each other. Then, a research was conducted by collecting samples of data to 100 respondents through questioner survey and interview. The format of questioner was designed by using design of experiment "FULL FACTORIAL" which consisted of 4 attribute and 2 levels at existing condition and hypotheses. The result of survey was processed by using Spreadsheet Software with a multiple linear regression model, where Y is the function of utilities to Tariff (X1), Distance (X2), Duration (X3) and Accessibility (X4). The results of survey show the majority of respondent characteristic are males and the range of age is between 26-43 years. They are commonly private employee, and their average income are about Rp. 2.000.000 – Rp. 3.000.000 per month. From the data analysis of stated preference, an equation model of Y = 2.9123 – 0.0005 (X1) – 0.0133 (X2) 0.0225 (X3) – 0.0208 (X4) was obtained, value of R2 was 0.70 and has qualified the statistical test. The model was more sensitive to change of distance and duration of parking. From the application of model pursuant to Willingness to Pay by service user at the CBD area of Padang, it was obtained that the tariff of parking are Rp. 3.198 for zone 1 and Rp. 2.392 for zone 2.